Arabic Translation, Validation and Cultural Adaptation of the 7-Item Hamilton Depression Rating Scale in Two Community Samples - Alhadi, Ahmad N. (Sultan Qaboos Univ Med J, 2018)
OBJECTIVES: Depression is a common mental disorder, the severity of which is frequently assessed via interview-based clinical scales such as the 7-item Hamilton Depression Rating Scale (HAMD-7). The current study aimed to translate and examine the validity of an Arabic version of the HAMD-7 scale. METHODS: This study took place between February and March 2016 in the Psychiatry Department of King Saud University, Riyadh, Saudi Arabia. The HAMD-7 scale was translated into Arabic using forward and backward translation methods. A total of 153 Arabic speakers were recruited to test the translated scale, including 57 medical students and 96 members of the general public. The Arabic version of the HAMD-7 scale was completed by trained investigators during face-to-face interviews with the participants. In order to assess convergent validity, participants also completed an Arabic version of the self-assessed Patient Health Questionnaire-9 (PHQ-9) scale. Subsequently, the test-retest reliability of the translated HAMD-7 scale was evaluated two weeks later during a second interview. RESULTS: Overall, HAMD-7 scores were positively correlated with PHQ-9 scores (r = 0.633–0.749). Moreover, the translated HAMD-7 scale proved to be reliable in terms of test-retest reliability (intra-class correlation coefficient: 0.807; P <0.001). With regards to internal consistency, the Cronbach’s α values ranged between 0.607–0.756. CONCLUSION: The Arabic HAMD-7 scale was found to be reliable and valid among two samples of Arabic speakers in Saudi Arabia. However, further research among Arab-speaking patients diagnosed with depression is needed in order to establish its usefulness in assessing the severity of depressive symptoms.